Quality Management of Islamic Homeschooling Services at Ahsani Community Learning Activity Center (PKBM) Bandung City - Dian; Dessy Afriyani; Afni Fauziyah; Ahmad Ghozali; Diana, Aan (Ta'dib, 2023)
This research aims to analyze the quality management of Islamic Homeschooling services at PKBM Ahsani, Bandung City. This type of research was descriptive qualitative. Data collection was conducted through interviews with PKBM leaders, teachers, and staff, direct observation of the learning process, and study of documents related to policies and curriculum. Qualitative data analysis through thematic analysis was conducted. This research found that first, PKBM Ahsani Bandung which provided Islamic Homeschooling services, needed to pay attention to the learning outcomes implemented, and paid attention to the quality of human resources, especially in terms of character and high creative ability. Service quality management was mandatory for PKBM considering the high desire of parents to obtain a good educational environment for their children. Second, The Blended Learning Learning Model was the choice of PKBM Ahsani in providing Islamic Homeschooling services because it was considered effective for the implementation of Islamic Homeschooling student equality education programs. Islamic Homeschooling could develop their own curriculum and had flexibility in Islamic Homeschooling time management so that the vision of Islamic Homeschooling could be achieved.